Students' Perception of the Use of Digital Storytelling in Teaching Reading Narrative Text - Ira Maisarah; Liza Hidayati (Journal of English for Specific Purposes in Indonesia, 2024)
This study aims to provide students' perceptions of how to use digital storytelling in the classroom to facilitate their understanding of reading narrative texts. The research sample consists of eighth-graders from the Islamic junior high school SMPIT IQRA. In this study, a quantitative approach was paired with a descriptive research strategy. Using a closed-ended questionnaire, the study's researchers gathered data on how students felt about the use of digital storytelling in the instruction of reading narrative texts. Descriptive statistics were also used to examine the data, and tables displaying and discussing the results were created. According to the findings, most students firmly agreed with the following: students should find learning and teaching enjoyable; students should be able to comprehend when reading narrative texts; and students should use digital storytelling in the classroom. In summary, students' favorable opinions on using digital storytelling in reading instruction help them understand how to read narrative texts.